2009
DOI: 10.1002/bio.1165
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and fluorescent properties of cerium(III) glutathione complex

Abstract: The cerium (III) glutathione complex was synthesized by the redox reaction of cerium (IV) with glutathione reduced (GSH) in aqueous solution. The Job-plots indicate an ML (L = GSSG) stoichiometry of the complex. The fluorescent properties of the compound were investigated. The as-prepared complex showed the characteristic maximum emission spectra of Ce(III) at 350 nm (λ(ex) = 255 nm). The fluorescence results show that the Ce(IV) ions are first reduced to Ce(III), and then form Ce(III) complex after reacting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…For these experiments, cysteine was used as a model. Han's experiments were adapted to detect Ce 3+ −disulfide complexes at pH 6.0−7.4, 47 and a lack of experimental artifacts was verified (Figure S5a,b, Supporting Information)…”
Section: ■ Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…For these experiments, cysteine was used as a model. Han's experiments were adapted to detect Ce 3+ −disulfide complexes at pH 6.0−7.4, 47 and a lack of experimental artifacts was verified (Figure S5a,b, Supporting Information)…”
Section: ■ Resultsmentioning
confidence: 87%
“…40 The possible reaction mechanism can be described as the formation of a disulfide bridge−Ce (III) complex after interaction between Ce(IV) and the thiol groups. 47 This interesting property was used here to show the formation of complexes between cerium and disulfide groups after interaction with pristine CeO 2 NPs. For these experiments, cysteine was used as a model.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Recently, it has been reported that the cerium(III) glutathione complex can be synthesized through the redox reaction of cerium(IV) with GSH reduced by chemical synthesis in aqueous solution. 27 Because of its similar electron structure with cerium, the chemical properties of europium are analogous to cerium. In addition, the p53 signaling pathway may be involved in the production of NADPH, which can readily catalyze the oxidative decarboxylation of malate to generate NADPH or NADP +39 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Glutathione as a bioactive tripeptide contains the reduced GSH and oxidized GSSG and has an important physiological effect in living systems. 27,28 Using these peculiarities, we have realized the special self-biosynthesis of gold and silver nanoclusters (NCs) 29,30 in cancer cells or tumor tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In general, emitters of chemiluminescence reaction systems with cerium(IV) ions can be classified into five groups Ce(III) [8], excited sulphur dioxide (SO 2 *), excited products of oxidation of determined substance [18,19], dimols of singlet oxygen [20,35] and fluorophores [6,9,14]. Cerium (III), which is formed by the reduction of cerium(IV), is a well-known fluorescent ion, with the maximum emission at λ~355 nm [41][42][43] and therefore, it is a possible CL emitter. Excited sulphur dioxide species (SO 2 *) emit weak light at 300-450 nm [44,45], therefore the compounds showing strong fluorescence, such as rhodamine B [28,46], quinine [29][30][31] or lanthanide ions [32] are introduced to many reaction systems containing Ce(IV) ions.…”
Section: Reaction Conditions and Species Emitted From CL Reaction Sysmentioning
confidence: 99%